Фізична природа часу релаксації водно-спиртових розчинів - Stula, Yu. M. (Publishing house "Academperiodika", 2018)
The kinetics of relaxation processes in aqueous alcoholic solutions has been studied. A modelfor the nonequilibrium state of those solutions is proposed, in which the slowest relaxationprocess is associated with the destruction of new phase nuclei. The process of their destructionis described in the framework of both the Lagrangian formalism with low dissipation and thenucleation theory. The self-diffusion coefficients of molecules from the nucleus surface arecalculated and used to estimate the lifetime of nuclei and its dependence on the nucleus size. Arelation between the diffusion coefficient of nuclei in the nucleus-size space and the coefficientof molecular self-diffusion from the nucleus surface is found. A comparison with availableexperimental data is made.